Perkembangan Identitas Psikologi Sosial Dalam Konseling Multibudaya - Bakhrudin All Habsy; Marissa Nabilla Putri Anwar; Lisa Septiani (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Identity as the essence of the person, is recognized as something that continues to develop despite being influenced by environmental and social factors. Social identity theory, which emphasizes the influence of social groups on self-concept, is an important foundation in understanding this dynamic. Multicultural counseling involves a deep understanding of the cultural characteristics of the counselee. This research uses qualitative methods with literature study techniques. The purpose of this research is to find out the social identity in multicultural counseling. The results of the study include: (1) social psychology identity development, (2) the context of the emergence of multicultural counseling, (3) multicultural conceptual development, and (4) the role of counselors in multicultural counseling social identity.